2021
DOI: 10.1038/s42003-021-02640-x
|View full text |Cite
|
Sign up to set email alerts
|

Low dose inocula of SARS-CoV-2 Alpha variant transmits more efficiently than earlier variants in hamsters

Abstract: Emerging variants of SARS-CoV-2 have been shown to rapidly replace original circulating strains in humans soon after they emerged. There is a lack of experimental evidence to explain how these natural occurring variants spread more efficiently than existing strains of SARS-CoV-2 in transmission. We found that the Alpha variant (B.1.1.7) increased competitive fitness over earlier parental D614G lineages in in-vitro and in-vivo systems. Using hamster transmission model, we further demonstrated that the Alpha var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
(12 reference statements)
0
17
0
Order By: Relevance
“…Some recent studies regarding transmissibility of Alpha variant or Alpha-like viruses showed a fitness advantage of these viruses on strains carrying D614G spike mutation in the hamster model. Using low-dose inocula in the hamster model, one study showed a superiority of Alpha variant when inoculated competitively and a more efficient transmission when inoculated alone 21 . This study reported that Alpha variant is slightly more excreted than G614 strain at the early stage of infection in hamsters, affecting viral transmission to contact animals.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies regarding transmissibility of Alpha variant or Alpha-like viruses showed a fitness advantage of these viruses on strains carrying D614G spike mutation in the hamster model. Using low-dose inocula in the hamster model, one study showed a superiority of Alpha variant when inoculated competitively and a more efficient transmission when inoculated alone 21 . This study reported that Alpha variant is slightly more excreted than G614 strain at the early stage of infection in hamsters, affecting viral transmission to contact animals.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these new variants, especially those classified as Variants of Concern (VOCs) by the World Health Organization, can transmit more easily [ 9 ]. Our previous study showed that the higher transmissibility of the Alpha variant correlated with a lower infectious dose in hamsters [ 10 ]. Furthermore, these VOCs have reduced susceptibility to neutralizing antibodies induced by natural COVID-19 infection or first-generation COVID-19 vaccines and have led to reinfections or vaccine breakthrough infections [ 11–13 ].…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 The model have been effectively used for the studies on the vaccines, antivirals, pathogenesis, transmissibility, virus shedding and disease severity associated with SARS-CoV-2 VOC's. 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 Recently, few studies have been published on the pathogenesis aspect of Omicron variant in mice and Syrian hamsters in comparison with other VOC's demonstrating decreased severity of infection. 23 , 24 , 25 , 26 , 27 , 28 , 29 Abdelnabi et al.…”
Section: Introductionmentioning
confidence: 99%